The Professionalism of Islamic Religious Education Teachers in Facing the Challenges of Digitalized Learning - Sepriadi; Ibrahim Gitarius; Faiz Roisuddun Hibatullah; Khairil Hafidz; Riky Supratama; Husna Nashihin; Liam A. Rutherford (Yayasan Azhar Amanaa Yogyakarta, 2025)
The transformation of digital education presents both challenges and opportunities for Islamic Religious Education (PAI) teachers, particularly in shaping students’ character. This study aims to examine the impact of learning digitalization on the role of PAI teachers, the challenges they face in mastering technology, and the strategies for developing digital-based learning at Tahfizhul Quran Al Kautsar School in Klaten. This research employs a qualitative case study approach through interviews, observations, and documentation conducted in June 2025. The findings indicate that digitalization has shifted the role of teachers to become more active facilitators. However, challenges such as low digital literacy and limited infrastructure remain significant obstacles. Solutions include training, the development of Islamic digital teaching materials, the use of appropriate platforms, and communication with students’ guardians. Collaboration among teachers, schools, and relevant stakeholders is essential to create innovative yet value-driven Islamic education.